Game changing strategies for retailers: How to create utilitarian offers for shoppers - Ahmed, S. (Institute of Electrical and Electronics Engineers Inc., 2015)
the purpose of this study is to investigate why shopper experiences cognitive dissonance in the aftermath of impulsive shopping and what should be the retailer's strategy on that. A qualitative phenomenological research method was undertaken. In-depth interviews were conducted. The analysis revealed five themes that highlight the shopper's impulsive shopping experiences. Themes were divided into textural and structural descriptions of the phenomenon. In textual description one theme emerged that illustrate shopper post impulsive shopping experience. In structural description four themes emerged in which shopper expressed that they forced to do impulsive shopping. Impulse shopping is a blessing for retailer's perspective, however, it has found that shoppers are smart they can track retailer's tactics that persuading to increase impulse shopping. Now it is a challenge for retailers to overcome the situation. In this context, this study also discussed how does retailers can maximize profit by using the insights from game theory to shape a game that is right for their shoppers. An idea of creating value and how to capture value through game changing were elaborated. Â© 2015 IEEE.